Strategies for surface coatings of implantable cardiac medical devices - Coronel-Meneses, David; Sánchez-Trasviña, Calef; Ratera, Imma; Mayolo-Deloisa, Karla (Frontiers in Bioengineering and Biotechnology, 2023)
Cardiac medical devices (CMDs) are required when the patient's cardiac capacity or activity is compromised. To guarantee its correct functionality, the building materials in the development of CMDs must focus on several fundamental properties such as strength, stiffness, rigidity, corrosion resistance, etc. The challenge is more significant because CMDs are generally built with at least one metallic and one polymeric part. However, not only the properties of the materials need to be taken into consideration. The biocompatibility of the materials represents one of the major causes of the success of CMDs in the short and long term. Otherwise, the material will lead to several problems of hemocompatibility (e.g., protein adsorption, platelet aggregation, thrombus formation, bacterial infection, and finally, the rejection of the CMDs). To enhance the hemocompatibility of selected materials, surface modification represents a suitable solution. The surface modification involves the attachment of chemical compounds or bioactive compounds to the surface of the material. These coatings interact with the blood and avoid hemocompatibility and infection issues. This work reviews two main topics: i) the materials employed in developing CMDs and their key characteristics, and ii) the surface modifications reported in the literature, clinical trials, and those that have reached the market. With the aim of providing to the research community, considerations regarding the choice of materials for CMDs, together with the advantages and disadvantages of the surface modifications and the limitations of the studies performed.